KONSTANTIN CHACHAVA - D. L. Kapanadze (IRBIS LLC, 2017)
The article describes the medical and scientific contribution of the outstanding Georgian obstetrician and gynecologist Konstantin Chachava as well as a historical sketch on the "Transcaucasian midwifery institute".